2008
DOI: 10.5465/ambpp.2008.33649817
|View full text |Cite
|
Sign up to set email alerts
|

Incompatible Assumptions: Barriers to Producing Multidisciplinary Knowledge in Communities of Scholarship.

Abstract: 1 We are indebted to Cailin B. Hammer for taking on the labor intensive and painstakingly detailed tasks of gathering all of the articles reviewed here, creating matrices for coding, conducting the citation count, and keeping the entire project organized. We could not have carried out this research without her able assistance. We would also like to thank Don Conlon and Deepak Malhotra for their helpful comments on earlier versions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2008
2008
2009
2009

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Strauss (1978) points out that negotiation outcomes are delimited by time and are eventually “reviewed, reevaluated, revised, revoked, or renewed,” (p. 5). Specific negotiations have a history and temporal dependence that most research ignores (for further discussion see Bendersky & McGinn, 2008; Okhuysen & Bonner, 2006; Okhuysen, Galinsky, & Uptigrove, 2003). There is not much behavioral work on how issues are renegotiated after one or another party finds that performance of the terms of the deal are simply not possible (economists have studied the question of what they call incomplete contracts; see, e.g., Guriev & Kvasov, 2005).…”
Section: Who What How When and Whymentioning
confidence: 99%
“…Strauss (1978) points out that negotiation outcomes are delimited by time and are eventually “reviewed, reevaluated, revised, revoked, or renewed,” (p. 5). Specific negotiations have a history and temporal dependence that most research ignores (for further discussion see Bendersky & McGinn, 2008; Okhuysen & Bonner, 2006; Okhuysen, Galinsky, & Uptigrove, 2003). There is not much behavioral work on how issues are renegotiated after one or another party finds that performance of the terms of the deal are simply not possible (economists have studied the question of what they call incomplete contracts; see, e.g., Guriev & Kvasov, 2005).…”
Section: Who What How When and Whymentioning
confidence: 99%
“…Research in this field has not had much impact on other areas of social science where negotiation is plainly crucial. Bendersky and McGinn (2008) found that scholars in organization science infrequently cite negotiation research even though the process itself is obviously crucial for organization design and function.…”
mentioning
confidence: 99%
“…Negotiation theory can benefit from the more “open systems” perspective of organization theories, particularly those that import social movement ideas from the environment. At the same time, while organizations are depicted as “negotiated orders,” the specificity of tactics uncovered in bounded negotiations can inform what that means and looks like (Bendersky & McGinn, 2008). Bringing together social movements and negotiations perspectives, we can examine more fine‐grained tactics than social movement theories typically address and more broadly situated issues than negotiation theories typically address.…”
Section: Between Social Movements and Negotiationsmentioning
confidence: 99%
“…Social movement theory has moved from a macro structural focus to greater inclusion of the micro dynamics of change (Scully & Segal, 2002). At the same time, negotiation theory is shifting its attention from the closed system of interpersonal bargaining to an “open systems” approach, which takes into account how resources from the social system affect particular negotiations and how the social system is itself a negotiated order (Bendersky & McGinn, 2008). Using concepts from the intersection of these theories, I interpret four instances in which employee groups came together to work across differences.…”
mentioning
confidence: 99%